2017
DOI: 10.1128/jvi.02128-16
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus (HCMV)-Specific CD4 + T Cells Are Polyfunctional and Can Respond to HCMV-Infected Dendritic Cells In Vitro

Abstract: Human cytomegalovirus (HCMV) infection and periodic reactivation are generally well controlled by the HCMV-specific T cell response in healthy people. While the CD8 ϩ T cell response to HCMV has been extensively studied, the HCMVspecific CD4 ϩ T cell effector response is not as well understood, especially in the context of direct interactions with HCMV-infected cells. We screened the gamma interferon (IFN-␥) and interleukin-10 (IL-10) responses to 6 HCMV peptide pools (pp65, pp71, IE1, IE2, gB, and US3, select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 70 publications
5
91
0
Order By: Relevance
“…We also wanted to measure the range of T cell responses in a large donor cohort to a number of viral proteins expressed during lytic infection; we have previously identified both CD4 + and CD8 + T cells producing IFNγ from many donors to six HCMV lytic proteins pp65, IE1, IE2, gB, pp71, and US3 (57, 63). Using FluoroSpot methodology, we were able to measure CD8 + T cell IFNγ responses and both IFNγ and IL-10 CD4 + T cell responses to overlapping peptide pools of these 11 HCMV proteins.…”
Section: Resultsmentioning
confidence: 99%
“…We also wanted to measure the range of T cell responses in a large donor cohort to a number of viral proteins expressed during lytic infection; we have previously identified both CD4 + and CD8 + T cells producing IFNγ from many donors to six HCMV lytic proteins pp65, IE1, IE2, gB, pp71, and US3 (57, 63). Using FluoroSpot methodology, we were able to measure CD8 + T cell IFNγ responses and both IFNγ and IL-10 CD4 + T cell responses to overlapping peptide pools of these 11 HCMV proteins.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that multifunctional cellular immune responses might be involved in the self‐cure process. Several studies have demonstrated the protective roles of host polyfunctional cells against numerous infectious organisms . For example, the frequency of Plasmodium falciparium ‐specific polyfunctional T cells has been associated with protection in humans .…”
Section: Discussionmentioning
confidence: 99%
“…The production of cellular IL-10 in response to HCMV antigenic stimulation by CD4+ T cells has been observed in multiple studies (Clement et al 2016; Jackson et al 2017a; Mason et al 2013; Schwele et al 2012). Production of IL-10 is a characteristic feature of regulatory T cells (Tregs) (Zhu et al 2010).…”
Section: Introductionmentioning
confidence: 94%
“…In order to address this problem, we have developed a viral dissemination assay which we have used to interrogate the capacity of HCMV-specific CD8+ (Jackson et al 2014) and CD4+ T cells (Jackson et al 2017a) to control the spread of HCMV in vitro. We have demonstrated that purified CD8+ and CD4+ T cell populations when isolated directly ex vivo are able to prevent the spread of the a GFP-tagged clinical CMV isolate.…”
Section: Current Research Perspectivesmentioning
confidence: 99%